2017
DOI: 10.1055/s-0043-104632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Intraluminal Contrast Enhancement in Patients with Spontaneous Cervical Artery Dissection: A Black-Blood MRI Study

Abstract: ZUSAMMENFASSUNGZiel Kürzlich durchgeführte Studien zeigten, dass intraluminale Thromben der A. carotis interna in black-blood (BB)-MRSequenzen eine Kontrastmittelaufnahme zeigen. Ziel der Studie ist es, die Wertigkeit der intraluminalen Kontrastmittelaufnahme bei Patienten mit einer spontanen arteriellen Dissektion der Halsgefäße zu untersuchen. Material und Methoden ABSTR AC TPurpose Recent studies have suggested that intraluminal thrombi show contrast enhancement on carotid black-blood T1w MRI. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…All imaging findings suspicious of cerebral vasculitis were documented. For diagnosis of arterial dissection, we routinely performed dissection sensitive MRI sequences (T1-weighted imaging with fat-saturation) ( 11 , 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…All imaging findings suspicious of cerebral vasculitis were documented. For diagnosis of arterial dissection, we routinely performed dissection sensitive MRI sequences (T1-weighted imaging with fat-saturation) ( 11 , 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, it cannot visualize wall structure, including hematoma. Multi-contrast high-resolution, cardiovascular magnetic resonance (hrCMR) has been increasingly used to characterize arterial abnormality by visualizing both lumen morphology and wall structure, including atherosclerosis, dissection and vasculitis [ 3 , 7 , 8 ]. Many pilot studies have demonstrated its complementary values for the diagnosis of intracranial dissection over DSA, magnetic resonance angiography (MRA) and computed tomography angiography (CTA) by harnessing its excellent soft tissue contrast [ 3 , 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 VWCE is evident in approximately two-thirds of dissections. 3,14,47,61 When present, this finding is thought to be due to inflammation, stasis of blood within the false lumen, or disruption of the vasa vasorum. 48,50 The enhancement pattern tends to be eccentric (< 50% circumference), 48,61 and may extend beyond the visualized dissection flap and/ or hematoma, suggesting farther-reaching injury to the intima than can be seen on noncontrasted sequences (Fig.…”
Section: Ca and Va Dissectionmentioning
confidence: 99%
“…3 Extensive enhancement in cervical dissections may be associated with a heightened risk of multiple dissections and stroke, raising the question of whether these patients have a more severe vasculopathy. 14,47 However, VWCE is not a specific indicator of dissection, because this finding can be seen in areas without other evidence of vessel pathology. 3 Whether this represents an underlying vasculopathy that predisposes to dissection remains unclear.…”
Section: Ca and Va Dissectionmentioning
confidence: 99%